FAKTOR - FAKTOR PENENTU MOTIVASI KERJA GEN Z DI PT INDOGUNA BALI - Nyoman Panji Kesuma; Ni Kadek Winda Yanti; I Gst. Ayu Wirati Adriati; Nuning Indah Pratiwi (CV. Lafadz Jaya, 2026)
Generational shifts in the workforce have become a significant challenge for organizations worldwide. Generation Z, born between 1997 and 2012, now dominates the workforce and is characterized by being tech-savvy, adaptable, and valuing work-life balance, job meaningfulness, and personal development. Work motivation is a crucial aspect as it directly affects productivity, loyalty, and organizational performance. PT Indoguna Bali, a premium food distribution company employing many Gen Z workers, faces the challenge of maintaining employee motivation amid the demands for work flexibility, technology integration, and adaptive leadership. This study aims to examine whether work-life balance, digital workplace environment, job meaningfulness, and leadership style individually influence the work motivation of Gen Z employees. A quantitative method was employed with a population of 55 Gen Z employees at PT Indoguna Bali. Data were collected through questionnaires and analyzed using SPSS version 26, including classical assumption tests and multiple linear regression analysis. The results indicate that work-life balance, digital workplace environment, job meaningfulness, and leadership style each significantly affect the work motivation of Gen Z employees at PT Indoguna Bali. Recommendations include improving work flexibility, enhancing digital technology, communicating job contributions, strengthening leader communication and engagement, and providing recognition and career development to boost motivation. Future research is suggested to include additional variables such as organizational culture, job satisfaction, or other psychological factors and to use a larger sample or longitudinal design for more generalizable and in-depth results.